Microglia-mediated inflammation and synaptic pruning contribute to sleep deprivation-induced mania in a sex-specific manner - Rong-Jun Ni; Wei-Jun Yuan; Yi-Yan Wang; Xiao Yang; Jin-Xue Wei; Lian-Sheng Zhao; Qiang Wang; Xiang-Dong Tang; Xiao-Hong Ma (Translational Psychiatry)
Abstract Sleep loss is a key trigger for a manic episode of bipolar disorder (BD), but the underlying microglial and molecular mechanisms remain unclear. Sleep loss induces microglial and inflammatory responses. Microglia, resident macrophages in the central nervous system, regulate synaptic pruning by engulfing dendritic spines. Here, we introduce a modified paradoxical sleep deprivation (SD) paradigm as a BD mouse model. After intermittent 16-h daily SD for 4 days, the mice showed mania-like behavior, reduced cytokine/chemokine production, mitochondrial damage, microglial loss, decreased synaptic engulfment by microglia, and synaptic gain. Single-nucleus RNA sequencing (snRNA-seq) revealed cell-type-specific inflammation- and synapse-related gene expression profiles in the prefrontal cortex (PFC) and hippocampus of SD-treated male mice. Interestingly, much more differentially expressed genes were observed in SD-treated female versus male mouse brain, especially in the PFC. Pharmacological depletion of microglia by colony stimulating factor-1 receptor (CSF1R) inhibitor PLX3397 blocked SD-induced inflammation-related and senescence-associated abnormalities in a sex-specific manner. Microglial elimination reversed SD-induced synapse gain and mania-like behavior in males but not in females. However, microglial inhibition by minocycline had no effect on SD-induced behaviors in a sex-independent manner. These findings demonstrate that microglia-mediated neuroinflammation and synaptic pruning contribute to SD-induced mania-like behavior in a mouse model of BD in a sex-specific manner.